The Intersection of Palliative Care and Interventional Radiology: Enhancing Understanding and Collaboration - Buss, Mary K. (Seminars in Interventional Radiology, 2017)
In the treatment of cancer patients, many interventional radiologic procedures are palliative in nature. The goal for these therapies is often something other than cure, such as prolonged survival or improved quality of life. The goals of therapy should be matched with the patient's wishes, and must include open communication between the health care provider and the patient. Hospice and palliative medicine is its own specialty, and a multidisciplinary approach to the care of cancer patients should include discussions with these health care specialists. This article will briefly define palliative care in general, describe the specialty of hospice and palliative medicine, and discuss how hospice differs from palliative care. Finally, it will highlight opportunities for interventional radiology specialists to incorporate more deliberately palliative care skills and competencies into their own practice and to collaborate with palliative care specialists.
Keywords: palliative care; quality of life; interventional radiology; cancer